Characteristics of the proximal to distal regions of the petioles to identify 15 tree species of Papilionoideae-Fabaceae - Heneidak, Samia; Shaheen, Abdel Samai M (Bangladesh Journal of Plant Taxonomy, 2007)
Comparative studies on the structure of the vascular supply of stem-leaf transitional zone of the petioles were carried out in 15 papilionoid tree species. Anatomical characteristics and changes in the main vascular trace were recorded. The anatomical features of significance include outline; epidermal cell; pericyclic fiber patterns; main petiolar vasculature; presence, number and separation of ridge vascular bundles; presence of additional accessory ridge bundles; crystal types; secretory elements and multicellular trichomes. Erythrina variegata and Pterocarpus indicus show no change in the petiole trace structure throughout their petioles from proximal to distal, while the rest of the species have minor to major changes. Sophora secundiflora has the highest number of ridge vascular bundles (5-6), while these are absent in the two Dalbergia species, E. variegata, Derris robusta, Sophora davidii and S. japonica. Only Derris robusta and Sophora japonica show unusual petiole trace structure by having two additional accessory ridge bundles adaxial of the main trace enclosing with it by a complete ring of pericyclic fibers. The studied species of tribe Millettieae show the presence of secretory cavities lined by epithelial cells. The usefulness of these character states is shown for assessing, identifying and delimiting these examined species. Key words: Accessory ridge bundles, Crystals, Papilionoideae, Petiole anatomy, Petiole vasculature, Ridge bundles, Secretory cavities DOI: 10.3329/bjpt.v14i2.530 Bangladesh J. Plant Taxon. 14(2): 101-115, 2007 (December)